2007
DOI: 10.1592/phco.27.12.1711
|View full text |Cite
|
Sign up to set email alerts
|

Candida Endophthalmitis: Focus on Current and Future Antifungal Treatment Options

Abstract: Candida endophthalmitis is a sight-threatening manifestation of disseminated candidiasis. The occurrence of endogenous candida endophthalmitis in patients with candidemia has ranged from 0-45% in the published literature. In critically ill patients, it has even been associated with increased mortality. In recent years, use of newer antifungal therapies for invasive candidiasis has increased given the rise in infections with non-albicans species of Candida. To identify current practices of the management of end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 77 publications
0
63
0
2
Order By: Relevance
“…Ocular infection caused by candidemia is well known (15,19,20). In one prospective study, the incidence of eye involvement was 16%, and that of endophthalmitis was 1.6% (15).…”
Section: Discussionmentioning
confidence: 99%
“…Ocular infection caused by candidemia is well known (15,19,20). In one prospective study, the incidence of eye involvement was 16%, and that of endophthalmitis was 1.6% (15).…”
Section: Discussionmentioning
confidence: 99%
“…This newer antifungal agent was therefore the first showing intraocular penetration due to lower protein binding and improved water solubility. However, fluconazole lacked a broad spectrum of coverage against many of the commonly encountered organisms found to cause fungal endophthalmitis [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Amphotericin B has been traditionally used for the treatment, either systemically or intravitreally usually injected at doses varying from 1 to 50 g. In one study with the application of escalating doses from 10, 20, 30 to 50 g, the 3 higher doses of amphotericin B appeared to be associated with stronger degrees of retinal toxicity [32] . Based on animal experiments, intravitreal amphotericin B in doses of 5 or 10 g remains an appropriate therapeutic option for patients with severe fungal endophthalmitis, for instance secondary to Aspergillus [32] .…”
Section: Quinolonesmentioning
confidence: 99%
“…A single intravitreal injection of fluconazole at a concentration of 100 g/ml and higher caused harmful retinal changes with disorganization of the photoreceptor outer segments [34] . Clinical experience revealed that intravitreal injection of 10 g/0.1 ml fluconazole may be the safe dosage for intraocular fungal infection [32] .…”
Section: Quinolonesmentioning
confidence: 99%